Asthma in Adolescents: A Randomized, Controlled Trial of an Asthma Program for Adolescents and Young Adults with Severe Asthma. Issue 4 (3rd August 2002) - Cowie, Robert L; Underwood, Margot F; Little, Cinde B; Mitchell, Ian; Spier, Sheldon; Ford, Gordon T
Abstract : BACKGROUND: Asthma is common and is often poorly controlled in adolescent subjects. OBJECTIVE: To determine the impact of an age-specific asthma program on asthma control, particularly on exacerbations of asthma requiring emergency department treatment, and on the quality of life of adolescents with asthma. METHODS: The present randomized, controlled trial included patients who were 15 to 20 years of age and had visited emergency departments for management of their asthma. The interventional group attended an age-specific asthma program that included assessment, education and management by a team of asthma educators, respiratory therapists and respiratory physicians. In the control group, spirometry was performed, and the patients continued to receive usual care from their regular physicians. The outcomes were assessed by a questionnaire six months after entry into the study. RESULTS: Ninety-three subjects entered the study and were randomly assigned to the intervention or control group. Of these, only 62 patients were available for review after six months. Subjects in both the control and the intervention groups showed a marked improvement in their level of asthma control, reflected primarily by a 73% reduction in the rate of emergency department attendance for asthma. Other indexes of disease control, including disease-specific quality of life, as assessed by questionnaires, were improved. There was, however, no discernible difference between the subjects in the two groups, with the exception of an improvement in favour of the intervention group in the symptom (actual difference 0.7, P=0.048) and emotional (actual difference 0.8, P=0.028) domains of the asthma quality of life questionnaire. The overall quality of life score favoured the intervention group by a clinically relevant difference of 0.6, but this difference did not reach statistical significance (P=0.06). CONCLUSIONS: Although all subjects demonstrated a significant improvement in asthma control and quality of life, the improvement attributable to this intervention was limited to two domains in disease-specific quality of life.